Hepatitis B Core-Related Antigen Stratifies the Risk of Liver Cancer in HBeAg-Negative Patients With Indeterminate Phase - Tseng, Tai-Chung; Hosaka, Tetsuya; Liu, Chun-Jen; Suzuki, Fumitaka; Hong, Chun-Ming; Kumada, Hiromitsu; Yang, Wan-Ting; Hsu, Chen-Yang; Su, Tung-Hung; Yang, Hung-Chih; Liu, Chen-Hua; Chen, Pei-Jer; et al. (The American journal of gastroenterology, 2022)
Many patients with chronic hepatitis B (CHB) are classified as indeterminate patients because they fall outside the defined CHB phases. We aimed to explore hepatocellular carcinoma (HCC) risk in hepatitis B e antigen (HBeAg)-negative patients with indeterminate phase and investigated whether the risk could be stratified by serum levels of hepatitis B core-related antigen (HBcrAg). Two retrospective cohorts enrolling HBeAg-negative, treatment-naïve CHB patients without cirrhosis were constructed (N = 2,150 in Taiwanese discovery cohort and N = 1,312 in Japanese validation cohort with a mean follow-up period of 15.88 and 12.07 years, respectively). The primary end point was HCC development. According to the American Association for the Study of Liver Disease guidelines, 990 (46%) HBeAg-negative patients had indeterminate CHB phase at baseline in the Taiwanese cohort. Compared with the patients with inactive CHB and those with immune-active CHB, the indeterminate patients exhibited intermediate but diverse risk of HCC. When HCC risk was stratified by a HBcrAg level of 10,000 U/mL, 10-year HCC cumulative incidence was 0.51% and 5.33% for low HBcrAg and high HBcrAg groups, respectively, with a hazard ratio of 4.47 (95% confidence interval: 2.62-7.63). This cutoff was validated to stratify HCC risk not only in different subgroup analyses but also in an independent Japanese cohort. Finally, the overall HBeAg-negative CHB patients could be simply reclassified into high-risk and low-risk groups by combining ALT, hepatitis B virus DNA, and HBcrAg levels in both cohorts. Serum HBcrAg level of 10,000 U/mL stratifies HCC risk in HBeAg-negative patients with indeterminate phase, which is useful for optimizing their clinical management.